Using Economic Evidence to Set Healthcare Priorities in Low‐Income and Lower‐Middle‐Income Countries: A Systematic Review of Methodological Frameworks. (25th January 2016) - Wiseman, Virginia; Mitton, Craig; Doyle‐Waters, Mary M.; Drake, Tom; Conteh, Lesong; Newall, Anthony T.; Onwujekwe, Obinna; Jan, Stephen
Abstract: Policy makers in low‐income and lower‐middle‐income countries (LMICs) are increasingly looking to develop 'evidence‐based' frameworks for identifying priority health interventions. This paper synthesises and appraises the literature on methodological frameworks – which incorporate economic evaluation evidence – for the purpose of setting healthcare priorities in LMICs. A systematic search of Embase, MEDLINE, Econlit and PubMed identified 3968 articles with a further 21 articles identified through manual searching. A total of 36 papers were eligible for inclusion. These covered a wide range of health interventions with only two studies including health systems strengthening interventions related to financing, governance and human resources. A little under half of the studies (39%) included multiple criteria for priority setting, most commonly equity, feasibility and disease severity. Most studies (91%) specified a measure of 'efficiency' defined as cost per disability‐adjusted life year averted. Ranking of health interventions using multi‐criteria decision analysis and generalised cost‐effectiveness were the most common frameworks for identifying priority health interventions. Approximately a third of studies discussed the affordability of priority interventions. Only one study identified priority areas for the release or redeployment of resources. The paper concludes by highlighting the need for local capacity to conduct evaluations (including economic analysis) and empowerment of local decision‐makers to act on this evidence.